PENGARUH GAMIFIKASI PADA IDU (ILEARNING EDUCATION) DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA - Untung Rahardja; Qurotul Aini; Hani Dewi Ariessanti; Alfiah Khoirunisa (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2018)
All fields have been supported by technology, especially in the world of education in the teaching and learning process to determine the quality of university graduates. In the world of education, Raharja College has implemented iLearning learning methods to achieve learning goals. Students are given learning experiences using the iLearning method which is a learning process using the Ten iLearning IT Pillars (TPI) media. However, iLearning learning is considered to be ineffective where many students do not communicate with lecturers as well as lack of information about lectures. Therefore, a new learning method is made for the teaching and learning process to be more effective and can be developed, the presence of gamification in online learning is to encourage students to be more enthusiastic as well as an alternative in organizing and conditioning learning situations to be more exciting and not monotonous, so that it can be fun and build character for students in participating in online lectures, the presence of a leaderboard in the form of a level of student activity is also useful to find out how active students are in working on assignments and understanding the lecture material provided by the lecturer.